An Assessing Speaking Ability: Insights from English Conversation Club among Fifth-Semester Midwifery Students - Harahap, Yulinda Oktaviana; Harahap, Yulina Oktaviani (Jurnal Educatio FKIP UNMA, 2024)
This study explores the speaking abilities of 5th-semester students involved in the English Conversation Club (ECC) within a Midwifery Diploma Study Program. The research focuses on understanding the challenges faced by students in speaking English and evaluating the ECC's contribution to enhancing their speaking skills. The investigation utilized a mixed-methods approach involving qualitative and quantitative data collection.The study found that while most students performed well, as indicated by their scores falling under the "Good" and "Very Good" categories, notable challenges persisted. Students encountered difficulties primarily related to vocabulary limitations, grammar intricacies, a lack of motivation, and psychological factors impacting their speaking performances.Factors influencing speaking abilities were analyzed through student interviews, highlighting vocabulary, grammar, and motivational issues as key hindrances. The ECC program was perceived positively by students, providing an environment conducive to English practice. However, the infrequent use of English beyond the ECC sessions limited its impact on students' overall speaking skills. To improve speaking abilities, interventions emphasizing vocabulary enhancement, grammar proficiency, motivational support, and better preparation strategies were recommended. Further emphasis on consistent English practice outside the ECC was suggested for more comprehensive improvement. In conclusion, while the ECC positively contributed to students' speaking proficiency, challenges related to vocabulary, grammar, motivation, and insufficient practice outside the program persist. Targeted interventions focusing on these areas are crucial to further enhance students' speaking abilities within the Midwifery Diploma Study Program.